2023
DOI: 10.15421/022323
|View full text |Cite
|
Sign up to set email alerts
|

Impacts on gut microbiota of rats with high-fat diet supplemented by herbs of Melissa officinalis, Lavandula angustifolia and Salvia officinalis

M. V. Bilan,
M. A. Lieshchova,
V. V. Brygadyrenko

Abstract: Medicinal plants are used in traditional, folk medicine and veterinary practice to treat and prevent exacerbations of chronic diseases, diseases of the cardiovascular and nervous systems, respiratory and digestive organs, liver, bile ducts, kidneys, urinary tract, to regulate metabolism and to boost immunity, etc. The therapeutic effect on the body is exerted by biologically active substances (alkaloids, glycosides, tannins, essential oils, and others) that are present in various parts of plants. Understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Indirect effect can be mediated by the suppression of certain microorganism types in the animal intestine. Thus, adding 5% of crushed dry young shoots of M. officinalis to the high-fat diet of laboratory rats significantly changed the quantitative ratio of Escherichia coli with normal and altered enzyme activity in the intestinal system (Bilan et al, 2023). The results of Zazharskyi et al (2019) showed that the ethanol extract of M. officinalis significantly inhibited Salmonella typhimurium colonies growth, slightly inhibited the growth of Escherichia coli, Klebsiella pneumonia, and Corinebacterium xerosis, and did not affect Proteus mirabilis, Listeria monocytogenes, and Candida albicans.…”
Section: Discussionmentioning
confidence: 97%
“…Indirect effect can be mediated by the suppression of certain microorganism types in the animal intestine. Thus, adding 5% of crushed dry young shoots of M. officinalis to the high-fat diet of laboratory rats significantly changed the quantitative ratio of Escherichia coli with normal and altered enzyme activity in the intestinal system (Bilan et al, 2023). The results of Zazharskyi et al (2019) showed that the ethanol extract of M. officinalis significantly inhibited Salmonella typhimurium colonies growth, slightly inhibited the growth of Escherichia coli, Klebsiella pneumonia, and Corinebacterium xerosis, and did not affect Proteus mirabilis, Listeria monocytogenes, and Candida albicans.…”
Section: Discussionmentioning
confidence: 97%
“…Cho et al (2006) reported that yeast extracts rich in nucleotides had a positive impact on the intestinal mucosa and its lymphoid formations, contributing to the development of local immunity. In recent years, the use of phytogenic feed additives, which contain a wide range of herbs, spices, and essential oils, has become relevant (Zazharskyi et al, 2019;Boyko et al, 2021;Lieshchova & Brygadyrenko, 2022Bilan et al, 2023). Scientists believe the possible mechanisms of action of plant extracts on animals are related to the intestinal microflora correction, increased absorption and nutrient assimilation, as well as pronounced antioxidant and immunomodulatory effects.…”
Section: Introductionmentioning
confidence: 99%